Estímulo mecânico na morfometria em mudas de Enterolobium contortisiliquum (Vell.) Morong - Volkweis, Cátia Raquel (2012)
This study aimed to quantify the effects induced by mechanical stimuli on the quality of seedlings Enterolobium contortisiliquum (Vell.) Morong. Treatments include five intensities of mechanical stimulation (0, 5, 10, 20 and 40 pushups) made daily for thirty days. The mechanical stimuli were initiated on December 20, 2011. Made by one-way passage of a structure composed by a bar PVC pipe arranged horizontally and secured on a metal frame with bearings. At the end of the imposition of the treatments evaluated the quality of the changes through increases in shoot height (H) and stem diameter (C) and quantified to root dry mass (RDM) , leaf (MSF) and (MSPA), and calculated the absolute growth rate (AGR), leaf area (LA), specific leaf area (SLA), leaf area ratio (LAR), weight of sheet (RPF) and proceeded to determine the loss of electrolytes from roots (PER). All measurements were performed in four replicates of five seedlings per treatment. At this stage, the test was conducted according to a completely randomized design with four replications. On January 20, 2012, after the end of treatments, some of the seedlings of treatment and control of seedlings to 20 pushups daily were transplanted to pots with a capacity of 5 liters filled with sand grain size of 2 mm and kept in en- vegetation for 39 days under water restriction. At this stage, we adopted the design of randomized blocks in a factorial arrangement (2 x 14) composed of two intensities of mechanical stimuli and thirteen evaluations on time with four replicates of five seedlings. Data were subjected to analysis of variance with the help SISVAR 5.0 statistical software (FERREIRA, 2007) and subsequently analyzed by linear regression at 5% probability. Seedlings monkfish-the-woods submitted to mechanical stimuli for 30 days during hardening subjected to 20 mechanical stimuli voiced daily values of morphometric variables and test the loss of electrolytes indicative of a higher quality changes over seedlings not mechanically stressed But without greater resistance to drought after planting